2004
DOI: 10.1554/03-499
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Adaptation and the Evolution of Basal and Maximum Rates of Metabolism in Rodents

Abstract: Abstract. Metabolic rate is a key aspect of organismal biology and the identification of selective factors that have led to species differences is a major goal of evolutionary physiology. We tested whether environmental characteristics and/or diet were significant predictors of interspecific variation in rodent metabolic rates. Mass-specific basal metabolic rates (BMR) and maximum metabolic rates (MMR, measured during cold exposure in a He-O 2 atmosphere) were compiled from the literature. Maximum (Tmax) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
201
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(215 citation statements)
references
References 122 publications
(249 reference statements)
11
201
2
1
Order By: Relevance
“…Nevertheless, results of conventional and phylogenetic analyses were largely congruent, with one interesting exception (see below). Although body mass showed significant phylogenetic signal, as has been reported previously for rodents and other animal groups Blomberg et al 2003;Rezende et al 2004), rodents categorized as aquatic (nutria, beaver, muskrat, water rat) were significantly larger in body mass as compared with species from all other habitat types. Thus, both ecology and phylogeny affect body size.…”
Section: Kidney Mass In Relation To Body Mass and Habitatsupporting
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, results of conventional and phylogenetic analyses were largely congruent, with one interesting exception (see below). Although body mass showed significant phylogenetic signal, as has been reported previously for rodents and other animal groups Blomberg et al 2003;Rezende et al 2004), rodents categorized as aquatic (nutria, beaver, muskrat, water rat) were significantly larger in body mass as compared with species from all other habitat types. Thus, both ecology and phylogeny affect body size.…”
Section: Kidney Mass In Relation To Body Mass and Habitatsupporting
confidence: 77%
“…As will be shown, our analyses were in fact able to demonstrate associations with habitat. Clearly, an improvement for future studies would be to obtain quantitative environmental measurements from at or near the capture sites of each species (Tieleman et al 2003;Rezende et al 2004).…”
Section: /3mentioning
confidence: 99%
“…A number of studies have suggested that BMR would likely show a correlated response to direct selection on MMR (Koteja, 1987;Bozinovic, 1992;Dohm et al, 2001;Rezende et al, 2004;Nesoplo et al, 2005a;Sadowska et al, 2005;Wone et al, 2009). Likewise many evolutionary models suggest complex interrelationships among traits linked to metabolic rates (Ricklefs and Wikelski, 2002;Downs et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, is there a universal metabolic scaling law, why is resting metabolism correlated with daily energy use in mammals but not birds, how did the diverse resting and maximal metabolic rates of animals evolve and is there a necessary correlation between resting and maximal aerobic metabolism in vertebrates (Ricklefs et al, 1996;Clavijo-Baque and Bozinovic, 2012)? Some of these questions are very difficult to answer but ecological and evolutionary physiologists have recently made increasing use of artificial selection experiments to test hypotheses about the phenotypic and genetic integration of energy metabolism (Swallow et al, 1998;Koch and Britton, 2001;Ksiażek et al, 2004;Rezende et al, 2004;Sadowska et al, 2005Sadowska et al, , 2008Swallow et al, 2009;Wone et al, 2009;Gebczyński and Konarzewski 2009a, b,). One of the foci of these recent studies has been testing hypotheses about the evolution of endothermy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the expectation that it would reflect some minimal level of homeostatic cellular processes, BMR shows tremendous variability both between and within species (McNab, 2005;Rezende et al, 2004;Snodgrass et al, 2005), raising two key issues: why does the variation exist and what are the functional implications of the variability? Clearly, an individual with a high BMR would need to feed for longer to fuel its metabolism than one with a low BMR.…”
Section: Introductionmentioning
confidence: 99%